Effectiveness of an intervention based on the nola pender model in promoting healthy lifestyles in peruvian universities [Efectividad de intervención basada en modelo de nola pender en promoción de estilos de vida saludables de universitarios peruanos] - Carranza Esteban, Renzo Felipe (2019)
ABSTRACT Introduction: Healthy lifestyles prevent diseases and optimize the health of the human being, even better among university students, who are vulnerable to changing attitudes, routines, habits, and their lifestyle. Objective: To determine the effectiveness of a program based on the Nola Pender model to promote healthy lifestyles in Peruvian university students. Methods: Pre-experimental study with pre-test and post-test, in a private university in Tarapoto, Peru, during 2017. 869 students from seven majors participated. To know the lifestyle of university students, the Pender PESPS-I was used. The intervention lasted eight months. Nutritional aspects, emotional health and physical activity were considered. In the statistical analysis, the non-parametric Wilcoxon test was performed, with a significance level of p=0.05, in addition to the distribution of absolute frequencies, percentages, means, average range and standard deviation. Results: The post-test measures were higher than to those of the pre-test, which demonstrated the effectiveness of the program to promote healthy lifestyles through exercising, health responsibility and stress management (p<0.05). However, in the dimensions nutrition, interpersonal support and self-update, no significant differences were found (p>0.05). Conclusions: The program to promote healthy lifestyles in Peruvian university students aged 16 to 22 years proved to be effective in improving exercise, health responsibility and stress management.